(untitled) ("Conference on Universal Science Research 2023", 2023)
Today, an important aspect of modern world linguistics is the absorption and interaction of scientific information that is inextricably linked with various fields of human activity. To provide students with thorough knowledge about the specific features of new directions in linguistics, such as ethnolinguistics, sociolinguistics, psycholinguistics, mathematical linguistics, computer linguistics, as a result of the interaction of linguistics with various scientific fields, and to boldly send young talents to these fields. must